Post-fire forest management effects on soil metal dynamics in Mediterranean forests - Ulus, Yener; Wang, Shaoyi; Tsz-Ki Tsui, Martin; Landau, Noah; Lekki, Owen; Bayazıt, Tuğba; Uzun, Habibullah; Aslan, Fevziye; Kavgacı, Ali (Frontiers in Environmental Science, 2025)
Wildfires are an integral component of Mediterranean ecosystems. The forest management practices implemented following such forest fires can significantly influence soil chemistry and metal dynamics. This study investigates the effects of different forest management strategies, including natural regeneration, grading (e.g., gradoni terrace making), and subsoiling with ripper on soil levels of major, trace, and heavy metals in a fire-affected forest in the southwestern part of Türkiye. Soil samples were collected 2.5 years after the containment of the wildfire and analyzed for selected metals (Fe, Ca, Al, Mn, Cr, Ni, Zn, Cu, Pb, Co, As, and Hg) concentrations. The findings indicated that subsoiling with a ripper resulted in elevated levels of multiple potentially toxic metals, including Cr (223.22 ± 60.47 mg/kg), Ni (150.54 ± 27.33 mg/kg), Zn (156.18 ± 66.14 mg/kg), and As (6.72 ± 1.30 mg/kg), compared to other treatments. These findings demonstrate that management interventions such as subsoiling with a ripper can significantly alter the distribution and concentration of trace metals. Future research integrating topographic variation and earlier sampling would further strengthen our understanding of post-fire metal dynamics.